Efficient sizing of single layer graphene oxide with optical microscopy under ambient conditions. (February 2020) - Luo, Qinmo; Wirth, Christopher; Pentzer, Emily
Abstract: Graphene oxide (GO) nanosheets are 2D particles with many advantageous properties including high gas barrier and mechanical strength, and can also be used as precursors to electronically conductive graphene-like structures. Characterizing the size of GO nanosheets is challenging because of the heterogeneous nature and ultra-thin 2D structure (∼1 nm). Current approaches for GO size measurements include atomic force microscopy (AFM) and scanning electronic microscopy (SEM), which both require significant time and environmental or financial resources. In response to these challenges, we herein report a facile method to size GO nanosheets using optical microscopy. As directly visualizing GO nanosheets is difficult due to poor contrast, we utilized the oil-water interfacial co-assembly of GO and charged particles to image single layer GO in situ . Contrast is generated between the 'dark' particles that occupy interstitial regions between 'light' GO nanosheets. The method allows GO to be imaged in a large area, in contrast to SEM and AFM, covering >200 nanosheets in one image. The size distribution of the nanosheets can be easily determined, giving results consistent to multiple SEM images. The novel method described herein is low cost and efficient, can be applicable to other 2D materials, and is amenable to manufacturing environments. Graphical abstract: Image 1